Profits may lead teams to lose matches, but scoring goals does not lead to profit - Luis Carlos Sánchez; Angel Barajas; Patricio Sanchez-Fernandez (European Research on Management and Business Economics (ERMBE), 2020)
The purpose of this paper is to examine the relationship between profitability and sporting performance in European football. Profitability has been rarely studied because it has not been considered an aim of European clubs, in contrast with American clubs. However, the emergence of investors who invest on both sides of the Atlantic shows that the objectives of owners can be diverse and that profitability has to be taken into account. The study of the compatibility or incompatibility of sporting performance and profitability has implications for the existence of clubs with owners with different objectives in the same competition, or even owners with different aims in the same club. The paper finds that financial performance has a negative influence on clubs' sporting performance, while sporting performance does not have a negative influence on profitability. Moreover, ownership concentration has a negative influence on both performance variables. These findings show that the pursuit of sport success could undermine the profitability and sustainability of clubs and that investors could focus less on sport results and focus more on maximizing the financial returns on their investments.
Keywords: G32; G34; L21; L25; L83; Z23; 650; Sports Finance; Firm Objectives; Firm Performance; Profitability